2016
DOI: 10.15252/emmm.201606743
|View full text |Cite
|
Sign up to set email alerts
|

ROCK signaling promotes collagen remodeling to facilitate invasive pancreatic ductal adenocarcinoma tumor cell growth

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a major cause of cancer death; identifying PDAC enablers may reveal potential therapeutic targets. Expression of the actomyosin regulatory ROCK1 and ROCK2 kinases increased with tumor progression in human and mouse pancreatic tumors, while elevated ROCK1/ROCK2 expression in human patients, or conditional ROCK2 activation in a Kras G12D/p53 R172H mouse PDAC model, was associated with reduced survival. Conditional ROCK1 or ROCK2 activation promoted invasive growth of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 77 publications
6
108
0
Order By: Relevance
“…Analyses on CDMs and in the liver demonstrated that priming with Fasudil alters KPC cell attachment, coordinated movement, and malleable spread of the tumor emboli, potentially via changes of the mechanical and biochemical properties of the host ECM, thereby altering ECM-cell interactions and durotaxis (93, 94). Furthermore, the Rho-ROCK-LIMK pathway drives path generation by leading tumor cells (66, 95), and hence, ROCK inhibition with Fasudil may inhibit path generation and coordinated cell movement of tumor cells in this context (95, 96). Additionally, priming with Fasudil may decrease cell survival in the bloodstream via impaired tolerance to shear stress (97).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses on CDMs and in the liver demonstrated that priming with Fasudil alters KPC cell attachment, coordinated movement, and malleable spread of the tumor emboli, potentially via changes of the mechanical and biochemical properties of the host ECM, thereby altering ECM-cell interactions and durotaxis (93, 94). Furthermore, the Rho-ROCK-LIMK pathway drives path generation by leading tumor cells (66, 95), and hence, ROCK inhibition with Fasudil may inhibit path generation and coordinated cell movement of tumor cells in this context (95, 96). Additionally, priming with Fasudil may decrease cell survival in the bloodstream via impaired tolerance to shear stress (97).…”
Section: Discussionmentioning
confidence: 99%
“…This signalling network is typically under tight regulation but can also be hyper‐activated by ECM remodelling. Aberrant activation of this signalling network leads to increased tumour invasiveness in pancreatic ductal adenocarcinoma (Rath et al, ) and squamous cell carcinoma (Figure D) (Samuel et al, ).…”
Section: Dysregulation Of Ecm‐mediated Signalling Network In Diseasementioning
confidence: 99%
“…Further assessment into the efficacy of FAK inhibition in the context of Merlin loss may still be of interest, particularly in pancreatic cancer where it has yet to be examined. It has recently been shown that using a short-term 'priming' treatment approach to inhibit ROCK signalling can reduce tissue stiffness, improve vascular patency, increase tumour perfusion, decrease in vivo primary tumour growth, metastasis and improve response to standard of care therapy [23,92], similar to chronic fasudil treatment [89]. Several inhibitors that target Rho GTPase or its downstream effectors including Rho-associated kinases (ROCK) have shown antitumour activity in preclinical models, which we have reviewed previously [87,88].…”
Section: Modulation Of the Upstream And Downstream Src Signalling Commentioning
confidence: 99%